Analisis Willingness to Pay (WTP) Pengunjung terhadap Pengembangan Kawasan Taman Wisata Alam (TWA) Gunung Meja - Meyanti Toding Buak; Bambang Nugroho; Nurhaidah Iriany Sinaga (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze visitors’ Willingness to Pay (WTP) and to estimate the economic value in supporting the development of Gunung Meja Nature Tourism Park (TWA) as a conservation area. This study employed the Contingent Valuation Method (CVM) with a total of 156 respondents. Data were analyzed using descriptive quantitative methods to obtain the average WTP value and its distribution. The results showed that the average WTP of visitors was IDR 19,300 per person, with the highest distribution in the range of IDR 10,000–30,000 and a dominant value of IDR 20,000 (23%). The estimated economic value of the area based on WTP reached IDR 3,939,245,800 per year, which is higher than the actual revenue of IDR 2,755,431,000 per year. The difference of IDR 1,183,814,800 indicates a potential increase in revenue through tariff adjustment. These findings indicate that visitors have a higher willingness to pay compared to the current tariff. Therefore, the WTP value can be used as a basis for determining optimal tariff policies to support sustainable management of conservation areas and to maintain their ecological functions.